PEMANFAATAN BUNGA PEPAYA SEBAGAI PRODUK BERNILAI JUAL TINGGI - Ahmad Jazuly Jazuly; Ade Irma Noviyanti; Pipit Rika Wijaya; Sugihartatik Sugihartatik (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2025)
Papaya (Carica papaya) is a plant that is widely found in Indonesia. Papaya flowers are rich in nutrients and have various benefits, both for health and for the culinary industry. Utilization of papaya flowers as a high-value product can be an opportunity to improve the community's economy, especially for farmers who have papaya plants but have not maximized other parts of the plant. During the training, participants were given steps in processing papaya leaves into Implementation Coordination: a) This community service is facilitated by the Jagatnata Maitreiya monastery which determines the training participants. b) The training participants were agreed to be groups of farmers and housewives in Jember. c) The training was carried out at the Jagatnata Maitreiya Jember monastery by providing materials on the benefits, efficacy of nutritional value and economic value. d) Evaluation of the implementation was carried out using direct interviews to find out feedback or expectations that had been achieved and desired by the participants.